2014
DOI: 10.1155/2014/454098
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition of Hydrocalumite over a Temperature Range of 400–1500°C and Its Structure Reconstruction in Water

Abstract: The thermal decomposition process and structure memory effect of hydrocalumite were investigated systematically for the first time over a wide temperature range of 400–1500°C. The calcined hydrocalumite samples and their rehydrated products were characterized by XRD, FT-IR, and SEM-EDX. The results show that the calcination products at temperatures ranging from 500 to 900°C are basically mayenite and lime, while one of the final products obtained by calcination at and above 1000°C is probably tricalcium alumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
(35 reference statements)
1
17
0
Order By: Relevance
“…The presence of hydrocalumite-like phases in the characterized samples was also confirmed by the XRD, as discussed as follows. Mayenite in the CaO-Al2O3 system is expected above 1300 ºC, therefore its presence at 700 ºC reinforces the hypothesis of hydrocalumite formation, as this phase decomposes close to 600 ºC resulting in CaO and C12A7 [17]. Additionally, it can be observed that not all initial materials reacted to form hydrocalumite-like phases.…”
Section: Figuresupporting
confidence: 75%
See 2 more Smart Citations
“…The presence of hydrocalumite-like phases in the characterized samples was also confirmed by the XRD, as discussed as follows. Mayenite in the CaO-Al2O3 system is expected above 1300 ºC, therefore its presence at 700 ºC reinforces the hypothesis of hydrocalumite formation, as this phase decomposes close to 600 ºC resulting in CaO and C12A7 [17]. Additionally, it can be observed that not all initial materials reacted to form hydrocalumite-like phases.…”
Section: Figuresupporting
confidence: 75%
“…OH -, CO3 2and Cl - [18,19]. This hydrate phase decomposes close to 600 ºC, resulting in lime (CaO) and mayenite (12CaO.7Al2O3 or C12A7) [17].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The reason is explained in the Supporting information (Part 4). When Ca-Al-LDH-900 was added into the boric acid solution, the following reaction occurs [46,47]: [49,50]. The boron species inside the aluminum gel and OH − in water can be immobilized as anions in the interlayer of LDHs:…”
Section: Discussionmentioning
confidence: 99%
“…Note that samples S-1 and S-2 contain a mineralogical phase with about 8 Å inter-planar spacing, identified as hydrocalumite (Ca 4 Al 2 (OH) 12 (Cl,CO 3 ,OH) 2 •4H 2 O) (see Table S1 in the additional supporting information), a layered double hydroxide (LDH) occurring in the mortars as a more stable hydration product (Tian and Guo 2014). Hydrocalumite is usually formed by the reaction between the portlandite (Ca(OH) 2 ) and the hydroxyaluminate (Al(OH) 4 À ) derived from the decomposition of clay impurities in the limestone (Tian and Guo 2014;Ponce-Antón et al 2018). It has generally been observed in ancient hydraulic mortars, as well as in modern pozzolanic cements and in dolomitic lime mortars (Rispoli 2017;Ponce-Antón et al 2018).…”
Section: Mineralogical Composition Of the Mortarsmentioning
confidence: 99%